Preservation and maintenance of wood-based structures of historic buildings: A systematic literature review on structural recovery techniques - Pedro Ignácio Lima Gadêlha Jardim; Sergio Neves Monteiro; Afonso Rangel Garcez de Azevedo; Victor Almeida de Araújo; Tulio Hallak Panzera; André Luis Christoforo (Case Studies in Construction Materials)
The recovery of heritage constructions is an important field of structural engineering, which aims the preservation of culture and history of ancient civilizations. Many recovery techniques can be applied to structural elements, although scientific literature is premised on preserving the original structure, whenever possible, avoiding the replacement of structural elements. This highlights the complexity of maintaining the original structure and ensuring an efficient engineering intervention. Different techniques were considered in literature under diverse contexts. In particular, the use of high-tech materials such as composites have been presented as an option alongside traditional solutions, such as steel and wood. Few publications are found on this topic and existing research tends to focus on isolated cases and lacks a broader systematic synthesis. Furthermore, no systematic literature review (SLR) dedicated specifically to wood-based structures in heritage buildings was identified in the literature prior to this work. This study fills the gap with a SLR that was carried out to map the diagnostic methods, recovery techniques, materials used, and performance outcomes, identifying the state of preservation and maintenance. The results show that: reinforcements with fiber-reinforced polymers (FRP), even at low ratios, consistently improved load capacity and stiffness; steel-based reinforcements showed higher variability in performance; visual inspection remains the most common diagnostic method, despite its limitations; replacement of original elements is sometimes inevitable, but strategies that preserve visual and material continuity are preferred.